2020
DOI: 10.1063/5.0031080
|View full text |Cite
|
Sign up to set email alerts
|

A study of photophoretic trapping exploiting motional resonances of trapped particles induced by wideband excitation

Abstract: Photophoretic forces confine particles by a combination of levitation and active trapping. To generate the latter, the component of photophoretic force transverse to gravity generates a torque, which leads to complex rotation of the particle, thereby generating a restoring force. This force has not been understood quantitatively. In this paper, we study this component of photophoretic force by trapping a single absorbing particle using a loosely focused Gaussian laser beam and modulating the trap-center spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…But, there exists no literature on how this efficiency of photophoretic force will change when we change the trapping beam profile. Earlier in our work, we have shown that micron sized absorbing particles can be trapped stably in a freespace gaussian beam 7 as well as in HG01 mode 8 . The photophoretic force has two components, one due to the difference in thermal accommodation coefficient across the surface of the particle, the FΔα force and another due to the uneven temperature distribution across the surface of the particle, the FΔT force 9 .…”
Section: Introductionmentioning
confidence: 51%
“…But, there exists no literature on how this efficiency of photophoretic force will change when we change the trapping beam profile. Earlier in our work, we have shown that micron sized absorbing particles can be trapped stably in a freespace gaussian beam 7 as well as in HG01 mode 8 . The photophoretic force has two components, one due to the difference in thermal accommodation coefficient across the surface of the particle, the FΔα force and another due to the uneven temperature distribution across the surface of the particle, the FΔT force 9 .…”
Section: Introductionmentioning
confidence: 51%
“…Since the light intensity is responsible for balancing gravity, a certain mass requires a specific laser intensity value for trapping, which is invariant, irrespective of the laser power. In our earlier work, 4 we have shown that changing the laser power translates the trapped particle to region where the intensity is the same. As a result, particles may be manipulated by changing both the laser intensity, as well as translating the laser beam.…”
Section: ■ Introductionmentioning
confidence: 88%
“…Since the light intensity is responsible for balancing gravity, a certain mass requires a specific laser intensity value for trapping, which is invariant, irrespective of the laser power. In our earlier work, we have shown that changing the laser power translates the trapped particle to region where the intensity is the same. As a result, particles may be manipulated by changing both the laser intensity, as well as translating the laser beam. In addition, the large magnitude of such forces promises a large number of very promising and diverse applicationsranging from three-dimensional displays to giant manipulation of particles to spectroscopy of aerosols and to atmospheric and bioaerosol science. …”
Section: Introductionmentioning
confidence: 99%
“…The particle sizes at each focal length are determined using the methodology described in Ref. [11].…”
mentioning
confidence: 99%
“…The photophoretic force is based on two types of forcestypically referred to in the literature as F ∆T and F ∆α [12]. Particles are confined in the axial direction due to F ∆T which balances gravity (F g ), while radially, a restoring force is generated by the helical motion of particles caused by the transverse photophoretic body force (F ∆α ), which applies a torque on particles due to its interaction with gravity [10,11]. Since it is basically the photophoretic ∆T force that balances gravity to cause axial trapping (or levitation), we determine this force using the multiphysics simulation software COMSOL.…”
mentioning
confidence: 99%